(untitled) (Global Journal of Human-Social Science, 2013)
The reform of institutional arrangements at the local level, especially the personalisation of executive power and the implementation of new options to participate, was expected to reinforce local democracy. However, there were doubts from the start as to whether this goal could be achieved, because institutional reforms were combined with the implementation of New Public Management. After more than a decade, an evaluation of the adopted measures in major western democracies seems appropriate. The comparative analysis draws on empirical studies conducted over three decades. Because of available data that is extremely difficult to compose for all western democracies, decision making procedures have been neglected in comparative empirical research. The evaluation presented here includes a puzzle of findings, which underpin future prospects of continuing reforms. The result is that a lack of accountability and control prevents democratization. Furthermore, measures taken to improve direct citizen participation have not achieved their goal.